Thymidine analog methods for studies of adult neurogenesis are not equally sensitive - Leuner, Benedetta (2009)
Adult neurogenesis is often studied by labeling new cells with the thymidine analog bromodeoxyuridine (BrdU) and using immunohistochemical methods for their visualization. Using this approach, considerable variability has been reported in the number of new cells produced in the dentate gyrus of adult rodents. We examined whether immunohistochemical methods, including BrdU antibodies from different vendors (Vector, BD, Roche, Dako, Novocastra, Accurate) and DNA denaturation pretreatments, alter the quantitative and qualitative patterns of BrdU labeling. We also compared the sensitivity and specificity of BrdU with two other thymidine analogs, iododeoxyuridine (IdU) and chlorodeoxyuridine (CldU). We found that the number of BrdU-labeled cells in the dentate gyrus of adult rats was dependent on the BrdU antibody used but was unrelated to differences in antibody penetration. Even at a higher concentration, some antibodies stained fewer cells (Vector, Novocastra). A sensitive BrdU antibody (BD) was specific for dividing cells; all BrdU-labeled cells stained for Ki67, an endogenous marker of cell proliferation. We also observed that DNA denaturation pretreatments affected the number of BrdU-labeled cells and staining intensity for a marker of neuronal differentiation, NeuN. Finally, we found that IdU and CldU, when used at molarities comparable to those that label the maximal number of cells with BrdU, are less sensitive. These data suggest that antibody and thymidine analog selection, as well as the staining procedure employed, can affect the number of newly generated neurons detected in the adult brain thus providing a potential explanation for some of the variability in the adult neurogenesis literature.